The Socio-Economic Impacts of Ebola in Liberia : Results from a High Frequency Cell Phone Survey - World Bank Group (Washington, DC, 2015)
As of February 18, 2015 Liberia has reported over 9,000 cases of Ebola Virus Disease (EVD), and 3,900 deaths. Since the previous round of data collection, in December 2014, Liberia continues to show progress toward getting to zero cases, and in the 21 days leading up to January 28, there were only 20 confirmed cases nationally, down from 92 in the 21 days ending on December 31, 2014, and a high of 546 in late August and early September. It is believed that all those currently infected are seeking care in Ebola Treatment Units (ETUs), some of which have begun to close in recent weeks as a result of declining need. The World Bank Group, with the Liberia Institute of Statistics and Geo-Information Services and the Gallup Organization, has continued to monitor the socio-economic impacts of EVD on households through a series of mobile-phone surveys conducted in October, November, and December 2014, and January 2015. As the health crisis continues to abate in Liberia, it will be crucial to tackle the important medium- and long-term economic and welfare impacts of Ebola on households. As Liberia continues on the path to eradicating Ebola, it will be important to identify and support those who are most vulnerable to the sluggish economy and whose long-term welfare may be negatively impacted by coping decisions made in the name of immediate stability. As households send their children back to school in the next month, the World Bank Group and partners will continue to monitor the crisis and work to support the Liberian government and its people as they move into economic recovery.